Health-related quality of life in a trial of acupuncture, sham acupuncture and conventional treatment for chronic sinusitis - Stavem, Knut (BioMed Central, 2008)
BACKGROUND: Acupuncture is commonly used to treat chronic sinusitis, though there is little documentation on the effect. This study presents the health-related quality of life (HRQoL) outcomes in a trial comparing traditional Chinese acupuncture, sham acupuncture, and conventional treatment for chronic sinusitis. FINDINGS: In a three-armed single blind randomized controlled study, we recruited 65 patients with symptoms of sinusitis >3 months and signs of sinusitis on computed tomography (CT). Patients were randomized to one of three study arms: (1) 2–4 weeks of medication with antibiotics, corticosteroids, 0.9% sodium chloride solution, and local decongestants (n = 21), (2) ten treatments with traditional Chinese acupuncture (n = 25), or (3) ten treatments with minimal acupuncture at non-acupoints (n = 19). Change in HRQoL was assessed over 12 weeks using the Chronic Sinusitis Survey (CSS) and Short form 36 (SF-36) questionnaires. In the study, we found only a non-significant difference on the CSS symptom scale between conventional medical therapy and traditional Chinese acupuncture. On the SF-36 scale role-physical the change was larger in the conventional group than in the sham group (p = 0.02), and on the mental health scale the change in the conventional therapy arm was larger than in the traditional Chinese acupuncture group (p = 0.03). There was no difference in effect on HRQoL on any scale between the sham and traditional Chinese acupuncture groups. CONCLUSION: There was no clear evidence of the superiority of one treatment over another on short-term HRQoL outcomes, although there was a statistically non-significant advantage of conventional therapy in a few dimensions.